What Makes the Grand Canyon Grand? : the world's most awe-inspiring natural wonders - Christian, Spencer; Felix, Antonia (New York : John Wiley, 1998)
Focuses on seven of the world's most famous natural wonders including Mount Everest, Victoria Falls, Grand Canyon, Carlsbad Caverns, Giant Redwoods, Paricutin Volcano, and the Nile River.
Includes index (P. 109-116)
Keywords: Landforms -- Juvenile literature; Natural monuments -- Juvenile literature; Landforms; Natural monuments